2022
DOI: 10.1111/psyg.12910
|View full text |Cite
|
Sign up to set email alerts
|

Addictive smartphone use in the elderly: relationship with depression, anxiety and sleep quality

Abstract: Background The aim of the present study was to explore the relationship between addictive smartphone use (ASU) and depressive symptoms, anxiety and sleep quality in elderly adults. Methods The study sample included smartphone users over the age of 65 years. The research data were obtained from social networking sites via a Google survey link. In addition to filling out a sociodemographic data form, the participants were also assessed with Smartphone Addiction Scale (SAS), Geriatric Depression Scale, Beck Anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…This phenomenon is closely tied to the widespread adoption of smartphones globally, as they surpass other information and communication technology devices (including desktop computers, laptops, and tablets, etc.) in terms of portability, immediacy, and convenience [ 55 , 56 ]. Consequently, smartphones have become the primary medium for accessing the internet and an integral component of contemporary life [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is closely tied to the widespread adoption of smartphones globally, as they surpass other information and communication technology devices (including desktop computers, laptops, and tablets, etc.) in terms of portability, immediacy, and convenience [ 55 , 56 ]. Consequently, smartphones have become the primary medium for accessing the internet and an integral component of contemporary life [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the Perceived Overload of short video apps for older adults had a significant negative impact on their loneliness and mental health, and these results confirmed that System Feature Overload, information overload, and social overload factors are linked to their negative emotions such as fatigue and frustration and also validated previous findings of the adverse effects of Perceived Overload factors on mental health. 6 , 8 , 29 , 47 , 83 In addition, the loneliness that occurs during the use of short video apps among older adults also exacerbates their mental health problems, thus elucidating the relationship between loneliness and mental health in terms of technological stress. 36 , 38…”
Section: Discussionmentioning
confidence: 99%
“… 34 Overuse may trigger mental health issues like depression and anxiety. 6 Research shows that short video apps effectively enhance older adults’ quality of life and mental health. 35 However, the perceived overload and negative mental health impacts should also be a concern.…”
Section: Literature Review and Research Hypotheses Formulationmentioning
confidence: 99%
See 2 more Smart Citations